Estrutura térmica identificada por transectos móveis e canal termal do Landsat 7 EM cidade tropical - Margarete Cristiane de Costa Trindade Amorim; João Lima Sant´Anna Neto; Vincent Dubreuil (Revista de Geografía Norte Grande, 2009)
This study aims to examine the thermal structure of the urban climate based on the interpretation of the satellite Landsat 7 (thermal channel) and measures for the area. It identifies how the production of urban climate develops based on an analysis of the structure of space forms and characteristics of land use and constructive materials in the generation of heat islands and their implications in environmental comfort in a tropical climate medium size city at Brazil. To check intra-urban air temperature, measures were carried out in mobile transects in the North-South and East-West routes. Thermal Channel data of Landsat-7, were converted to surface values. The results showed that the pattern of urbanization and characteristics of land use are responsible for the distribution of temperature generating heat islands in downtown and popular densely built neighborhoods. In those cases the highest indexes of social segregation added to higher temperature also provokes elevation in the number of illnesses and morbidity cases, mostly of respiratory diseases.